Limitations and consequences caused by work-related diseases in the worker’s lives - Bruna Caroline Rodrigues; Carla Caroline Campanelli Moreira; Taise Andréa Triana; Juliana Furlan Rabelo; Ieda Harumi Higarashi (Rev Rene)
This study aimed to investigate the impacts of work-related diseases in the worker’s lives, as well as analyze the contributions of studies to the nursing science, especially in the area of occupational health nursing. It is an integrative review with the following guiding question: What are the limitations and consequences caused by cumulative trauma disorders (CTD) in the worker’s lives reported in the nursing scientific production during the last five years (2006 to 2010). The descriptors used were: Cumulative Trauma Disorders and Occupational Health. We selected 14 articles and these were grouped according to common purposes, main limitations and consequences of CTD, and relevant information to contributions of studies in the area of Occupational Health Nursing. We concluded that the scientific production on this subject brings few effective contributions, and that further studies are needed to subsidize care strategies aimed at promoting health and quality of life of these workers.